Membangun Harmoni Dan Toleransi Melalui Moderasi Beragama - Agus Arifand; Salsabila Enggar Fathikasari; Meytri Kurniasih; Novi Fitriyani Rahmadani; Aprilia Putri; Agus Andrian Setiawan; Aissya Shifa Oktania; Adelia Eka Rachmadian (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
Religious moderation refers to a balanced and moderate approach in carrying out religious beliefs. This involves tolerance, understanding, and respect for the different beliefs and practices of other religions. Religious moderation seeks to offer dialogue and cooperation between adherents of different religions, with the aim of creating a harmonious and respectful society. Religious moderation is an important approach to building an inclusive, harmonious and peaceful society. This encourages mutual understanding, tolerance, and constructive dialogue between adherents of different religions. By fighting religious moderation, we can build a world that is more tolerant and respectful of religious differences. Religious moderation is a very important concept in religious life. This concept explains the importance of maintaining balance and proportionality in religion, and respecting existing religious differences. In religious moderation, one is expected to understand that all religions have the same values, such as love, tolerance and justice. Thus, religious moderation can help create peace and harmony between religious communities. By practicing religious moderation, a person can become more open, tolerant and wise in religion, and is able to build harmony between religious communities. Even though it has its own challenges, religious moderation remains the right solution to prevent extremism and fanaticism in religion, and to build a harmonious and peaceful society